2007
DOI: 10.1111/j.1399-3046.2006.00669.x
|View full text |Cite
|
Sign up to set email alerts
|

Unexpectedly high inter‐ and intrapatient variability of Ganciclovir levels in children

Abstract: Few studies report Ganciclovir or Valganciclovir levels in children. Single-center, retrospective study of all available Ganciclovir levels in transplanted children. Ganciclovir monitoring was performed as previously described [G. Filler (1998); Pediatric Nephrology, 12, 6]. For the normalization of dosing to GFR and target trough levels, we assumed first-order kinetics. We analyzed 57 Ganciclovir levels in 20 children (mean age 8.6 +/- 5.5 yr) treated with intravenous or oral Ganciclovir or oral Valganciclovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…
interindividual heterogeneity has previously been described 15 and suggests the need for drug monitoring, particularly in the case of viral failure or toxicity. 16 The need for routine drug monitoring is less clear due to the lack of established PK-PD parameters for preemptive strategy in pediatric practice.
…”
mentioning
confidence: 88%
“…
interindividual heterogeneity has previously been described 15 and suggests the need for drug monitoring, particularly in the case of viral failure or toxicity. 16 The need for routine drug monitoring is less clear due to the lack of established PK-PD parameters for preemptive strategy in pediatric practice.
…”
mentioning
confidence: 88%
“…Studies have shown significant pharmacokinetic variability depending on the child’s age, weight, and creatinine clearance, suggesting that pediatric dosing should take into account those parameters and may need pharmacokinetic monitoring (10, 11). Vaudry et al (12) recently reported good tolerance of oral valganciclovir in a pediatric solid-organ transplant cohort (n=63) at doses based on body surface area and creatinine clearance: 11% of patients were reported as having serious adverse events, most commonly hematologic laboratory abnormalities, and no patients were found to have CMV disease.…”
mentioning
confidence: 99%
“…Although a significant difference was only seen between median peak levels in those aged <6 months old compared with adults, the lowest median levels were actually noted in the 5-18 year age group. Low trough levels have been previously reported in a small study of paediatric transplant patients, with levels <0.5 mg/L being significantly more common in younger patients [12]. The observation that fewer babies <28 days had trough levels <0.5 mg/L compared with the overall age group <6 months would be in keeping with the almost exclusive renal excretion of GCV and the known immature renal function Peak levels were also in keeping with those reported in other clinical studies and were well above the MIC and IC 50 observed in vitro [6,7].…”
Section: Discussionmentioning
confidence: 58%
“…Given that such algorithms do not currently exist for i.v. GCV, and the wide interpatient and intrapatient variability reported in younger children when weight alone is used for dosing, TDM may be of particular benefit to guide GCV dosing in the paediatric age group [12]. We propose that TDM should be considered in M a n u s c r i p t M a n u s c r i p t A c c e p t e d M a n u s c r i p t b Includes those babies <28 days of age.…”
Section: Discussionmentioning
confidence: 99%